2022
DOI: 10.3389/fmolb.2022.918346
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Significance of GM3 Ganglioside Molecular Species With a Particular Attention to the Metabolic Syndrome Focusing on Toll-Like Receptor 4 Binding

Abstract: GM3 ganglioside, the first molecule in ganglioside family biosynthesis, is formed by transfer of sialic acid to lactosylceramide. Several dozen GM3 molecular species exist, based on diversity of ceramide structures. Among ceramide structures composed of sphingosine and fatty acids, there is a great diversity resulting from different combinations of chain length, hydroxylation, and unsaturation of fatty acid chains. Expression patterns of GM3 species in serum vary during pathogenesis of metabolic syndrome. Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Long-chain GM3 variations (16:0 and 18:0) have been used to inhibit inflammatory cytokine production in cases of chronic inflammatory disease ( 10 ). GM3 species have a key role in regulating inflammatory processes ( 15 , 16 ). GM3 species are correlated with insulin resistance, hypercholesterolemia, and the mediation of pro- or anti-inflammatory mechanisms by influencing toll-like receptors and consequently the production of pro-inflammatory cytokines ( 10 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long-chain GM3 variations (16:0 and 18:0) have been used to inhibit inflammatory cytokine production in cases of chronic inflammatory disease ( 10 ). GM3 species have a key role in regulating inflammatory processes ( 15 , 16 ). GM3 species are correlated with insulin resistance, hypercholesterolemia, and the mediation of pro- or anti-inflammatory mechanisms by influencing toll-like receptors and consequently the production of pro-inflammatory cytokines ( 10 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…For cells to have the very-long-chain fatty acids identified in the ceramide components of GM3, cellular very-long-chain fatty acid (VLCFA) elongases (ELOVL1-7) had to catalyze the elongation of the typical fatty acids synthesized [ 128 ]. In the early stages of metabolic syndrome, there is an increase in proinflammatory VLCFAs (22:0, 23:0, 24:0, h24:0) in serum and adipose tissue [ 129 ]. In severe obesity and metabolic syndrome, macrophage expression of VLCFAs decreases due to steroid regulatory element-binding protein SREBP1-induced reprograming of lipid synthesis [ 130 ].…”
Section: Contribution Of Glycan and Ceramide To Gg Functionmentioning
confidence: 99%
“…The effect of this change on GG function remains unknown. Human milk [133] Primarily C24:0,24:1, shorter chains not effective [106], predominantly ≥ C20 [133] d18:1 > d20:1 in human milk [133] Outside-in signaling [106,134]; skin problems, atherosclerosis, mitochondrial disfunction [135] GM3 H 1 : adipose, muscle, liver + serum [127,129]; mature outer retina [136] Primarily C18,22,24,24:1 w9 [137] d18:1 [137,138] d20:1 predominant in pyramidal and granular layers of the dentate gyrus [139] Type 2 diabetes, metabolic disease, and innate immune response [127][128][129] GD3 Prevalent in neuronal stem cells [140] Plasma membrane cytoplasm, ER-mitochondria-associated membranes [141] Longer-chain fatty acids > C18:0 in adult human brain [142] d18:1 > d20:1 Enhances proliferation via its roles in signal transduction (for a review, see [143])…”
Section: Contribution Of Glycan and Ceramide To Gg Functionmentioning
confidence: 99%
“…However, we and others showed that D-PDMP not only inhibited the activity in purified human kidney LacCer synthase and reduced LacCer generation, but also in various organs derived from multiple animal models of cardiovascular disease and T2D [ 16 , 61 ]. The pathophysiological role of GM3 involving toll like receptor-4 binding in adipose tissue in metabolic syndrome has been elegantly shown recently [ 62 ].…”
Section: Sphingolipid Inhibitors Mitigate the Pathology Of Insulin Re...mentioning
confidence: 99%